Expression of FHIT genes in CIN and cervical carcinoma and the relationship between FHIT gene and p53 and HPV16/18 - Zhang, Wen-Miao; Shuai, Ci-Xia; Zheng, Fei-Yun; Huang, Yin-Ping; Wang, Qun-Ji; Zhu-Hua; He, Qiu-Xiang (Zhōnghuá zhŏngliú zázhì, 2006)
To investigate the role and significance of FHIT genes depletion, p53 overexpression and HPV16/18 infection in cervical intraepithelial neoplasia (CIN) and cervical carcinoma (CC). Tumor samples taken from 52 cases of CIN and 69 cases of CC were processed by immunohistochemistry (SP) to determine the expression of FHIT genes and p53 protein, by in situ hybridization to detect HPV16/18 infection, and were compared with those in 18 cases of normal cervical tissues as control. (1) The FHIT expression was positive in normal cervical tissue with no depletion occurred, and was 30.8% in CIN. It was significantly higher in CIN III and carcinoma groups than that in normal and CIN I/II groups (P < 0.01). The depleted expression of FHIT in infiltrating cervical carcinoma group was 66.7% (46/69), significantly higher than that in normal and CIN groups (P < 0.01). Along with the decreasing of cell differentiation, the negative rate of FHIT raised. (2) The positive expression of p53 in CC group was 56.5% (39/69) and the HP